2018
DOI: 10.31025/2611-4135/2019.13817
|View full text |Cite
|
Sign up to set email alerts
|

The Actual Impact of Waste-to-Energy Plant Emissions on Air Quality: A Case Study From Northern Italy

Abstract: In recent decades there has been an intense debate about the impact of waste-to-energy (WTE) plant emissions on air quality, and therefore on public health. Currently available data from emissions inventories show the negligible impact of waste incineration on air quality. A number of impact assessment studies are currently available too. A few of them are site-specific, but none of them makes a direct comparison between the local impact of the emissions from a WTE plant and emissions from other "common" sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The contribution of WtE plant emissions was practically negligible, as suggested by the 0.07% maximum value for the ratio between estimated and observed daily mean concentrations. Similar contributions to the annual mean of NO 2 (0.08 µg m −3 ) and PM10 (5.2 × 10 −4 µg m −3 ) were estimated by dispersion modelling for the emissions of a WtE plant with the same features (daily waste throughput, emission control technology, stack height) located near Milan [19]. a 5 × 10 −4 µg m −3 contribution to the annual average concentration (Figure 5c,d).…”
Section: Air Quality Monitoring Site R1supporting
confidence: 68%
See 1 more Smart Citation
“…The contribution of WtE plant emissions was practically negligible, as suggested by the 0.07% maximum value for the ratio between estimated and observed daily mean concentrations. Similar contributions to the annual mean of NO 2 (0.08 µg m −3 ) and PM10 (5.2 × 10 −4 µg m −3 ) were estimated by dispersion modelling for the emissions of a WtE plant with the same features (daily waste throughput, emission control technology, stack height) located near Milan [19]. a 5 × 10 −4 µg m −3 contribution to the annual average concentration (Figure 5c,d).…”
Section: Air Quality Monitoring Site R1supporting
confidence: 68%
“…Air quality monitoring and robust modelling, based on both accurate emissions assessment and proper atmospheric dispersion calculations, are required for a comprehensive evaluation of the real environmental impact of WtE plants and to correctly assess the related health risks correctly. Accurate model results can help in (i) estimating the contribution of the plant's emission to the current levels of air pollution and (ii) comparing the role of the WtE source with all the other sources affecting local air quality (i.e., traffic, domestic heating or biomass burning), which are often mistakenly considered as less harmful to human health by public perception [19]. Indeed, health risk assessment studies for new plants are usually based on the maximum mass flow rate of pollutants and provide upper-bound estimates of the impact of the WtE plants on air quality.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report compiling data on the emissions to the atmosphere from 70 different WtE plants in the US provided evidence that atmospheric emissions for all criteria pollutants were significantly below the maximum achievable control technology (MACT) standard, with the exception of nitrogen oxides (NOx), whose emissions were 35 % below the emission limits ( 10 ). These results were confirmed by other reports which did not find a relationship between the level of dioxin emissions from WtE plants and their concentrations in the surrounding ambient air ( 11 , 12 ).…”
Section: Health Impacts Of Wte Plantssupporting
confidence: 91%
“…The fact that modern WtE plants are not associated with adverse environmental and health effects has been con rmed by several systematic reviews (Campo et were more than 70% below the Maximum Achievable Control Technology (MACT) standard for all criteria pollutants, except for nitrogen oxides (NO x ) which is emitted at 35% below emission limits (Castaldi 2021). In addition, these ndings have been corroborated by studies that have found no correlation between the magnitude of dioxin emissions from WtE plants and their ambient air concentration in the vicinity of the plants (Lonati et al 2019;Lonati, et al 2022). Thus, public fears about the impact of modern WtE plants on air quality are largely based on perceptions rather than facts.…”
Section: Introductionmentioning
confidence: 74%